Attenuation of γ-aminobutyric acid (GABA) transaminase activity contributes to GABA increase in the cerebral cortex of mice exposed to β-cypermethrin. (March 2014) - Han, Y; Cao, D; Li, X; Zhang, R; Yu, F; Ren, Y; An, L
The current study investigated the γ-aminobutyric acid (GABA) levels and GABA metabolic enzymes (GABA transaminase (GABAT ) and glutamate decarboxylase (GAD)) activities at 2 and 4 h after treatment, using a high-performance liquid chromatography with ultraviolet detectors and colorimetric assay, in the cerebral cortex of mice treated with 20, 40 or 80 mg/kg β-cypermethrin by a single oral gavage, with corn oil as vehicle control. In addition, GABA protein (4 h after treatment), GABAT protein (2 h after treatment) and GABA receptors messenger RNA (mRNA) expression were detected by immunohistochemistry, Western blot and real-time quantitative reverse transcriptase polymerase chain reaction, respectively. β-Cypermethrin (80 mg/kg) significantly increased GABA levels in the cerebral cortex of mice, at both 2 and 4 h after treatment, compared with the control. Also, GABA immunohistochemistry results suggested that the number of positive granules was increased in the cerebral cortex of mice 4 h after exposure to 80 mg/kg β-cypermethrin when compared with the control. Furthermore, the results also showed that GABAT activity detected was significantly decreased in the cerebral cortex of mice 2 h after β-cypermethrin administration (40 or 80 mg/kg). No significant changes were found in GAD activity, or the expression of GABAT protein and GABAB receptors mRNA, in the cerebral cortex of mice, except that 80 mg/kg β-cypermethrin caused a significant decrease, compared with the vehicle control, in GABAA receptors mRNA expression 4 h after administration. These results suggested that attenuated GABAT activity induced by β-cypermethrin contributed to increased GABA levels in the mouse brain. The downregulated GABAA receptors mRNA expression is most likely a downstream event.